Starch Synthesis in Ostreococcus tauri: The Starch-Binding Domains of Starch Synthase III-B Are Essential for Catalytic Activity - Barchiesi, Julieta; Velazquez, Maria Belen; Palopoli, Nicolas; Iglesias, Alberto A.; Gomez-Casati, Diego F.; Ballicora, Miguel Angel; Busi, Maria Victoria (Frontiers in Plant Science, 2018)
Starch is the major energy storage carbohydrate in photosynthetic eukaryotes. Several enzymes are involved in building highly organized semi-crystalline starch granules, including starch-synthase III (SSIII), which is widely conserved in photosynthetic organisms. This enzyme catalyzes the extension of the α-1,4 glucan chain and plays a regulatory role in the synthesis of starch. Interestingly, unlike most plants, the unicellular green alga Ostreococcus tauri has three SSIII isoforms. In the present study, we describe the structure and function of OsttaSSIII-B, which has a similar modular organization to SSIII in higher plants, comprising three putative starch-binding domains (SBDs) at the N-terminal region and a C-terminal catalytic domain (CD). Purified recombinant OsttaSSIII-B displayed a high affinity toward branched polysaccharides such as glycogen and amylopectin, and to ADP-glucose. Lower catalytic activity was detected for the CD lacking the associated SBDs, suggesting that they are necessary for enzyme function. Moreover, analysis of enzyme kinetic and polysaccharide-binding parameters of site-directed mutants with modified conserved aromatic amino acid residues W122, Y124, F138, Y147, W279, and W304, belonging to the SBDs, revealed their importance for polysaccharide binding and SS activity. Our results suggest that OT_ostta13g01200 encodes a functional SSIII comprising three SBD domains that are critical for enzyme function.